EFFECTIVENESS OF SUB ZONE CETACEAN PROTECTION IN MARINE PROTECTED AREAS SAVU SEA NATIONAL MARINE PARK, EAST NUSA TENGGARA - Mujiyanto Mujiyanto; Adriani Sri Nastiti; Riswanto Riswanto (COJ (Coastal and Ocean Journal), 2017)
The zonation review and evaluation took into account habitat protection areas and categorised migration routes. In addition, the sustainability of fishery resources is maintained, as people in Savu Sea depend on fishery resources. The objectives of this research are to analyse the effectiveness of sub-zone cetacean protection for Savu Sea National Marien Park. The research stations were watering inside and outside in Savu Sea National Marine Park. The sampling of the research was conducted on 2015 and 2016, collecting data using a zig-zag transect by observation method of collecting data sighting cetacean with single observer platform. The results of sub-zone cetacean protection against Southwest Sumba waters, West Sumba and East Timor Land need to be reviewed if referring the current zoning area. Sub-zone for areas to protect sustainability cetacean need to be adjusted addition and alteration of fishery zone, the area of Southwest Sumba, West Sumba and Central Sumba is ± 445,567.44 ha and ± 239,307.52 ha to around East Timor Land waters. Extensive re-evaluation of existing protection sub-zones is requiring. A review of extent to efectiveness water areas attend the conflict of interest in needs of fisherman to catch and migration route of cetacean.